REVERSE LOGISTICS: PERSPECTIVES, EMPIRICAL STUDIES AND RESEARCH DIRECTIONS - Jayant, Arvind (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
Environmental and economic issues have significant impacts on reverse logistics practices in supply chain management and are thought to form one of the developmental cornerstones of sustainable supply chains. Perusal of the literature shows that a broad frame of reference for reverse logistics is not adequately developed. Recent, although limited, research has begun to identify that these sustainable supply chain practices, which include the reverse logistics factors, lead to more integrated supply chains, which ultimately can lead to improved economic performance. The objectives of this paper are to: report and review various perspectives on design and development of reverse SC, planning and control issues, coordination issues, product remanufacturing and recovery strategies, understand and appreciate various mechanisms available for efficient management of reverse supply chains and identify the gaps existing in the literature. Ample opportunities exist for the growth of this field due to its multi-functional and interdisciplinary focus. It also is critical for organizations to consider from both an economic and environmental perspective. The characteristics of reverse logistics provided here can help the researchers/practitioners to advance their work in the future. Significance: The objective of this study is to encourage and provide researchers with future research directions in the field of reverse logistics for which only empirical research methods are not appropriate. In addition, the research directions suggested in the paper address several opportunities and challenges that currently face business managers & academicians operating in closed loop supply chain management. Keywords: Reverse supply chain management, Remanufacturing, Recycling, Reverse logistics.